Instrumen Kepuasan Mahasiswa Universitas Swasta Dengan Menggunakan Pemodelan Rasch - Rais Hidayat; Eka Suhardi; Yuyun Elizabeth Patras (Universitas Kristen Satya Wacana, 2019)
Student satisfaction at a university could predict the continuity of the university. Therefore understanding and improving student satisfaction needs to be done. This study provides an alternative model of student satisfaction instruments at private universities. The research methodology consists of a series of literature reviews, interviews, expert validation and testing the validity of the instrument using the Rasch model. The respondents of this study were 543 students from 6 faculties in a private university. Research findings include: (1) student satisfaction instrument models; (2) items that are difficult to approve; and (3) items perceived differently based on respondents' demographics. This research has implications for the management of private universities to improve some domains of student satisfaction.